# Solve for V V=L(r^2*arccos(1-h/r)+(h-r) square root of 2rh-h^2)

V=L(r2⋅arccos(1-hr)+(h-r)2rh-h2)
Simplify each term.
Factor h out of 2rh-h2.
Factor h out of 2rh.
V=L(r2arccos(1-hr)+(h-r)h(2r)-h2)
Factor h out of -h2.
V=L(r2arccos(1-hr)+(h-r)h(2r)+h(-h))
Factor h out of h(2r)+h(-h).
V=L(r2arccos(1-hr)+(h-r)h(2r-h))
V=L(r2arccos(1-hr)+(h-r)h(2r-h))
Apply the distributive property.
V=L(r2arccos(1-hr)+hh(2r-h)-rh(2r-h))
V=L(r2arccos(1-hr)+hh(2r-h)-rh(2r-h))
Apply the distributive property.
V=L(r2arccos(1-hr))+L(hh(2r-h))+L(-rh(2r-h))
Simplify.
V=Lr2arccos(1-hr)+Lhh(2r-h)-Lrh(2r-h)
Reorder 1 and -hr.
V=Lr2arccos(-hr+1)+Lhh(2r-h)-Lrh(2r-h)
Reorder L and r2.
V=r2Larccos(-hr+1)+Lhh(2r-h)-Lrh(2r-h)
Reorder 2r and -h.
V=r2Larccos(-hr+1)+Lhh(-h+2r)-Lrh(2r-h)
Reorder L and h.
V=r2Larccos(-hr+1)+hLh(-h+2r)-Lrh(2r-h)
Reorder 2r and -h.
V=r2Larccos(-hr+1)+hLh(-h+2r)-Lrh(-h+2r)
Move L.
V=r2Larccos(-hr+1)+hLh(-h+2r)-rLh(-h+2r)
Solve for V V=L(r^2*arccos(1-h/r)+(h-r) square root of 2rh-h^2)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top